Analysis of The Profitability of Agricultural Sector Companies - Sub-Sector of Agriculture Listed in Indonesia Stock Exchange - Tokit Masditok; Sriwardani Sriwardani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to analyze the profitability of plantation sub-sector companies listed on the Indonesia Stock Exchange (BEI), based on the analysis of Gross Profit Margin (GPM), Nett Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE). The data used in this research is secondary data in the form of financial statements of Plantation Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2018, which were obtained from www.idx.co.id. The method used in this research is the descriptive analysis based on quantitative/financial analysis. The results showed that companies with higher Total Assets and Total Equity have the potential to achieve better Total Revenue, thus supporting the achievement of better Earning After Tax (EAT). However, these conditions do not necessarily guarantee that the company will achieve the best Gross Profit Margin (GPM), Nett Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) as well, given the best Gross Profit Margin (GPM), Nett Profit Margin (NPM), Return On Asset (ROA) and Return On Equity (ROE) are financial ratios whose measurements are influenced by the width of the range or margin among other financial measures that underlie the calculation of these ratios.